Lopo sebagai Simbol Demokrasi Lokal pada Masyarakat Adat Atoin Pah Meto: (Studi Tentang Rumah Adat Lopo sebagai Simbol Demokrasi Lokal di Desa Saenam Kecamatan Miomaffo Barat Kabupaten Timor Tengah Utara) - Esrah D.N.A.Benu; Diana S.A.N Tabun; Yeftha Y. Sabaat (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This research is entitled Lopo as Symbol of Local Democracy in the Atoin Pah Meto indigenous Community” (Study of the Lopo Traditional House as a Symbol of Local Democracy in Saenam Village, Miomaffo Barat District, North Central Timor Regency). The main problem in this research is how Lopo as a symbol of local democracy in the lives of the Atoin Pah Meto indigenous community. The purpose of this research is to analyse and describe Lopo in the lives of the Atoin Pah Meto indigenous community. This research uses  qualitative methods. Data were collected through interviews, observations, and dokumentation with traditional leaders, religious leaders, village government officials, yo uth, womwn, and the community. Data analysis was conducted by systematically reviewing and interpreting field data. The finding reveal that lopo is not merely a place for storing harvests, but also serves as a central space for deliberation in resolving social, cultural, and political issues. It open structure without walls symblolizez valuesnof openness, equality, and participation. The local democratic values embodied in lopo include family values (mutual cooperation, solidarity, kinship), cultural values (traditional rituals, marriage, harvest celebrations), and political valuess (consensus, adherence to customary rules, and equality in decission making). Therefore, lopo is not only a cultural heritage but also a symbol of local democracy that strengthens the identity and social cohesion of the Atoin Pah Meto community.